Robust Statistics Analysis of Proficiency Test Result of Cement - Vashishtha, Shwet; Prasad, D. V. S.; Lokesh, R. N. (AMC Indian Journal of Civil Engineering, 2019)
A proficiency testing scheme for cement testing according to IS specifications was set up for cement testing laboratories in India. Proficiency testing schemes are inter-laboratory performance comparisons allowing participants to evaluate themselves against pre-established criteria. Proficiency testing is a powerful tool to help laboratories improve their performance as well as demonstrate their competences to accreditation bodies or customers. 24 cement testing laboratories participated in this program. Proficiency test results of physical test parameters of Ordinary Portland Cement-53 grade were obtained through organizing and performing the cement proficiency test plan. After performing the robust statistical analysis of the results, the test proficiency of the laboratory is evaluated.